A study of short term cognitive outcome in post cabg patient - Yusuf, Azlina (2013)
To evaluate the outcomes on short-term cognitive function in post CABG patients and to identify its risk factors. This is a prospective cohort study. Forty three patients subjected for CABG between March 2011 to July 2012 were enrolled in this study. Their cognitive function preoperative and 1 week postoperatively were documented with CANTAB®. The sociodemographic, medical and procedure characteristics were recorded in the data form. The total of 40 patients’ cognitive function were assessed and recorded before operation and at 1 week interval after CABG. There were impairment noted (>20% from baseline value) in three subtest of CANTAB® during post-operative period, with Intra/Extradimensional (IED) test 35% (n=14), Paired Associate Learning (PAL) test 35% (n—14) and Stop Signal Task (SST) test 27.5% (n—11) of the total subject. There were no significant correlation of these cognitive changes (P>0.05) with few variables such as age, education level, type of procedure, duration of anesthesia, surgery, CPB and rewarming, and also rate of rewarming. A presence of cognitive decline at 1 week interval post-operatively was observed among patient subjected for CABG. The main domains involved were executive function and visual memory. Thus pre-procedural details should be address to the patients in term of this neurocognitive impairment. In this study, there was no confounding factor noted related to cognitive changes.